Characterization and comparison of whey proteomes from bovine and donkey colostrum and mature milk. (15th March 2022) - Li, Mohan; Dong, Yushi; Li, Weixuan; Shen, Xinyu; Abdlla, Rayhnigul; Chen, Jiali; Cao, Xueyan; Yue, Xiqing
Abstract: As a small species of milk source, donkey milk has attracted widespread attention due to its high nutritional value. However, its composition is substantially different from the most widely consumed milk source—bovine milk. This study was aimed to conduct a qualitative proteomic analysis of donkey whey proteins (DWPs) and bovine whey proteins (BWPs). Specifically, 981, 988, 1127, and 1534 whey proteins were characterized in donkey colostrum (DC), donkey mature milk (DM), bovine colostrum (BC), and bovine mature milk (BM), respectively. Among these, 477 common whey proteins were identified in the four groups, whereas 43, 27, 105, and 476 unique whey proteins were identified in DC, DM, BC, and BM, respectively. The potential functions of these proteins, as well as the pathways involved, were further analyzed using bioinformatics. Our results provide a comprehensive understanding of the compositions of DWPs and BWPs and provide a theoretical basis for the development of whey protein nutrition. Highlights: ● 981, 988, 1127, and 1534 whey proteins were identified in DC, DM, BC, and BM. ● 477 common whey proteins were identified in the four groups. ● The top 10 enriched GO terms of whey proteins for each groups were analyzed. ● The top 15 pathways of whey proteins for each groups were performed.